The Burden Leprosy Diseases in India: A Study with Special Reference to Tamilnadu and their Districts (Indian Journal of Public Health Research & Development, 2020)
Background: Leprosy is one of the oldest diseases known to mankind. Despite the advancements made byscience and technology, this curable disease remains misunderstood and dreaded. India is home to the largestnumber of new leprosy cases globally. Tamilnadu is one among state of high level of leprosy cases in India.The country was still seen to have largest number of leprosy patients in 2018 especially female and children.Keeping this view, “The Burden Leprosy Diseases in India: A study with special reference to Tamilnadu andtheir Districts” was undertaken.Data and Method: The paper uses the secondary data from Report of the National Leprosy EradicationProgramme, Ministry of Health and Family Welfare and other research studies and carries out the bi-variateanalysis to realise its objectives.Findings and Suggestion: The Tamilnadu contribution of growth of leprosy diseases was continuouslydecreased because our government will take more steps to reduce the number of leprosy cases. Then only itis possible to reach less than one like Kerala and Punjab. Chennai (9.07%), Erode (9.93%) and Villupuram(9.48%) are the large number new leprosy cases deducted district in Tamilnadu. The budget allocation ofTamilnadu share was very low than the other states in India for the purpose of treatment of leprosy diseases.Government will educate the female and children to prevent from the communicable diseases like leprosy.
Keywords: Leprosy, Communicable Diseases, Prevalence Rate, Tamilnadu.